Alcohol complexing agents influence bacterial α-cyclodextrin production. (January 2021) - Li, Caiming; You, Yuxian; Lu, Zi; Gu, Zhengbiao; Hong, Yan; Cheng, Li; Ban, Xiaofeng; Li, Zhaofeng
Abstract: Cyclodextrin is widely used in the food industry due to its excellent physicochemical properties. Organic solvents are usually used as complexing agents in the enzymatic production of cyclodextrin. Because they form inclusion complexes with the cyclodextrin products, these solvents reduce product inhibition, change the product (α-, β- and γ-cyclodextrins) ratio and increase the cyclodextrin yield. In this study, the effects of twenty five alcohols, including linear and branched-chain monohydric alcohols and diols, on the yield and cyclodextrin ratio were systematically investigated. The stability of the inclusion complexes formed were also measured and compared. Although almost all of the alcohols increased cyclodextrin yield and many increased α-cyclodextrin selectivity, the effects of linear monohydric alcohols on α-cyclodextrin synthesis were greater than those of the branched-chain monohydric alcohols and diols with similar numbers of carbon atoms. The linear alcohols also showed the best correlation between inclusion complex formation and increased α-cyclodextrin selectivity. This study provides a theoretical basis for the selection of compound agents in producing α-cyclodextrin. Highlights: Linear monohydric alcohols (>8 carbon atoms) promoted α-cyclodextrin yield better. Lower branch degree of alcohol was more beneficial for α-cyclodextrin production. Larger molecular size of alcohol was more unfavorable to α-cyclodextrin production. Greater inclusion stability constant was better for α-cyclodextrin production.